Advances and Applications of Cellulose Bio-Composites in Biodegradable Materials - Chen, Zhen; Aziz, Tariq; Sun, Hongyue; Ullah, Asmat; Ali, Amjad; Cheng, Li; Ullah, Roh; Khan, Farman Ullah (Journal of polymers and the environment, 2023)
Cellulose is a natural polymer that has a lot of potentials. Cellulose gained more interest owing to its renewability, non-toxicity, economic value, biodegradability, high mechanical properties, high surface area, and biocompatibility. New sources, new isolation processes, and new treatments are currently under development to satisfy the increasing demand for producing new types of bio-based materials on an industrial scale. This article discusses the fundamentals and latest breakthroughs in cellulose biopolymer materials used in the fabrication of composite films owing to the cellulose forming films. Bio-polymers are finding wide applications due to their intrinsic properties such as low density, low thermal conductivity, corrosion resistance, and ease of manufacturing complex shapes. Cellulose possesses a highly crystallized structure, hence it is insoluble in typical organic solvents. Environmental restrictions are increasingly stringent, which is a key element leading to the growth of studies on this subject. These hydrocolloids have been modified by taking advantage of their valuable features; the mechanical strength and water resistance of cellulose make it being used as a thickener for large-scale applications such as cellulose composite films can extend the shelf life of a product while maintaining its biodegradability. New materials with high values are a hot topic for future research with commercial interest. These composite film potentials are contributing to the bio-economy. Here, the emphasis on the potential application of bio-composites of cellulose in various industries has been discussed. Graphical Abstract